2013
DOI: 10.1371/journal.pone.0065108
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Protection of Combined Probiotic Conditioned Media against Neonatal Necrotizing Enterocolitis-Like Intestinal Injury

Abstract: Balance among the complex interactions of the gut microbial community is important for intestinal health. Probiotic bacteria can improve bacterial balance and have been used to treat gastrointestinal diseases. Neonatal necrotizing enterocolitis (NEC) is a life-threatening inflammatory bowel disorder primarily affecting premature infants. NEC is associated with extensive inflammatory NF-κB signaling activation as well as intestinal barrier disruption. Clinical studies have shown that probiotic administration ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 76 publications
0
45
0
1
Order By: Relevance
“…These effects might be mediated by products secreted by probiotic bacteria. Probiotic conditioned media contain secreted products, free of intact bacteria, and it was recently reported that this media reduces NEC-like intestinal damage in an animal model [35]. Probiotic conditioned media inhibites the NF-κB signaling pathway and its proinflammatory cytokine production [36], which contributes to attenuating the intestinal inflammatory response [36].…”
Section: Discussionmentioning
confidence: 99%
“…These effects might be mediated by products secreted by probiotic bacteria. Probiotic conditioned media contain secreted products, free of intact bacteria, and it was recently reported that this media reduces NEC-like intestinal damage in an animal model [35]. Probiotic conditioned media inhibites the NF-κB signaling pathway and its proinflammatory cytokine production [36], which contributes to attenuating the intestinal inflammatory response [36].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive discussion is beyond the scope of this review and unfortunately we seem no closer to a definitive answer despite large-scale trials, such as ProPrems [82] and PIPS [83]. Hopefully, mechanistic studies [84,85,86,87] together with a more detailed understanding of the microbiome and its influence on the development of NEC (referred to above) will help us find a way out of this impasse.…”
Section: Preventionmentioning
confidence: 99%
“…31 The potential mechanisms by which probiotics may prevent NEC have been extensively studied in experimental animal models. 86,[104][105][106][107][108][109][110][111][112][113][114][115][116] Specifically, their effect on TJs has been studied by a number of laboratories. In 2009, Khailova, at al., published that oral administration of Bifidobacterium bifidum (Bb) decreased elevated protein levels of ileal occludin and claudin-3 observed in neonatal rats with NEC.…”
Section: Development Of the Intestinal Epithelial Barriermentioning
confidence: 99%
“…69 A separate group showed Bifidobacterium infantis (Bi) preserved the intestinal barrier during experimental NEC in mice by allowing occludin and claudin-4 to localize appropriately at the TJ. 80 In a particularly elegant study, Shiou, et al, 106 , found neonatal rats with NEC given conditioned media from combinations of Lactobacillus plantarum, Lactobacillus acidophilus and Bifidobacterium infantis cultures were protected from intestinal barrier dysfunction and maintained ZO-1 at the TJ. A small clinical trial also confirmed that probiotics can also improve intestinal barrier function by reducing intestinal permeability in premature infants 64 and this may be a mechanism by which probiotics can reduce NEC in premature infants.…”
Section: Development Of the Intestinal Epithelial Barriermentioning
confidence: 99%